2013
DOI: 10.1002/14651858.cd008201.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for implementation of thromboprophylaxis in hospitalized medical and surgical patients at risk for venous thromboembolism

Abstract: Interventions for implementation of thromboprophylaxis in hospitalized patients at risk for venous thromboembolism (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 94 publications
3
54
0
5
Order By: Relevance
“…Numerous interventions have been proposed to improve VTE prophylaxis prescription, such as electronic alert systems, an opt-out thromboprophylaxis policy, performance evaluation and feedback, as well as practitioner education. [13][14][15][16][17] Although electronic prescription alerts and performance reviews are not be feasible in our setting, the inclusion of a risk assessment sheet on the inpatient prescription charts and providing continuous practitioner education are interventions that should be considered for improving VTE prophylaxis prescription. With such a high percentage of patients at risk, an opt-out policy of thromboprophylaxis prescription should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous interventions have been proposed to improve VTE prophylaxis prescription, such as electronic alert systems, an opt-out thromboprophylaxis policy, performance evaluation and feedback, as well as practitioner education. [13][14][15][16][17] Although electronic prescription alerts and performance reviews are not be feasible in our setting, the inclusion of a risk assessment sheet on the inpatient prescription charts and providing continuous practitioner education are interventions that should be considered for improving VTE prophylaxis prescription. With such a high percentage of patients at risk, an opt-out policy of thromboprophylaxis prescription should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Para mejorar la adherencia a la aplicación de las GPC se han obtenido resultados favorables con la aplicación de TIC, además del uso de métodos tradicionales (difusión presencial, sesiones educativas) (26) . En un estudio en el que se comparó la enseñanza tradicional (libros, folletos) con el envío de información a través de mensajes de texto, este último resultó tener mayor tasa de aprendizaje entre los médicos residentes de un servicio de ginecoobstetricia (27) .…”
Section: Discussionunclassified
“…33 The implementation of system-wide VTE assessment interventions was the subject of a Cochrane meta-analysis, which included 54 studies of quality improvement initiatives. 34 The authors found that there was a statistically significant improvement in prophylaxis administration with the institution of computerized alerts, provider education, and multifaceted interventions. The combination of multifaceted interventions with electronic alerts was most effective.…”
Section: Quality Improvement Initiativesmentioning
confidence: 99%